Influence of the North Pacific Victoria Mode on the Madden–Julian Oscillation - Wen, Tao; Chen, Quanliang; Li, Jianping; Ding, Ruiqiang; Tseng, Yu-heng; Hou, Zhaolu; Li, Xumin (Frontiers in Earth Science, 2020)
Using the observational data and the Coupled Model Intercomparison Project Phase 5 (CMIP5) models to show the influence of the North Pacific Victoria mode (VM) on the Madden–Julian Oscillation (MJO) are examined in this analysis. The results show that the February–April (FMA) VM had a significant influence on the development and propagation of the MJO over the equatorial central–western Pacific (ECWP) during spring (March–May) between 1979 and 2017. Specifically, MJO development was favored more by positive VM events than negative VM events. One probably description for these complicated connections is that the SST gradient anomalies associated with positive VM events enhance the convergence of low-level over the ECWP, which, combined with the warm SST anomalies (SSTAs) in the equatorial central Pacific that lead to a boost in the Kelvin wave anomalies, results in the enhanced MJO activity over the ECWP. These conclusions indicate that the VM is an important factor in MJO diversity.